TEACHER’S EFFORTS TO DEVELOP THE CHARACTER OF ELEMENTARY SCHOOL STUDENTS THROUGH CHILD-FRIENDLY EDUCATION - Suci Muzfirah; Frenky Mubarok; Muasromatul Azizah; Muhammad Afdal (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2025)
Every human being has various characters, especially children in elementary school. Children aged 7-12 years are in the